Delayed versus on arrival modified live viral vaccination in stocker cattle on bovine respiratory disease - Ambs , Ashlee; Moberly, Heather; Capik, Sarah (Veterinary Evidence, 2022)
PICO question In auction market calves at high risk of developing bovine respiratory disease (BRD), does delayed (14–30 days) vaccination with a modified live vaccine (MLV) for viral respiratory pathogens versus administration of MLV on arrival (within 24 hours of arrival) to the stocker operation, result in less calves with BRD morbidity diagnosed based on visual signs and rectal temperature >40°C, or less calves with BRD mortality? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Four papers were critically reviewed. All were randomised complete block designs Strength of evidence Moderate Outcomes reported In stocker calves, delaying administration of a MLV for respiratory viruses may result in numerically lower initial BRD morbidity rates, while giving at arrival may result in numerically lower BRD retreatments. One study shows statistically lower cases of BRD morbidity after the third antimicrobial treatment in cattle vaccinated on arrival with both a clostridial and MLV for respiratory viruses compared to cattle vaccinated on arrival with clostridial vaccine and delayed MLV for respiratory viruses. No conclusion about mortality can be drawn due to inconsistent numerical conclusions between studies Conclusion Due to conflicting evidence and a general lack of statistically significant differences in morbidity and mortality outcomes, a definite answer regarding the impact of delayed MLV respiratory vaccination in stocker calves cannot be made How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.